2018
DOI: 10.3892/etm.2018.6846
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin reverses the dysfunction of human umbilical vein endothelial cells induced by angiotensin II

Abstract: Statins exert pleiotropic effects on endothelial cells, in addition to lowering cholesterol. This study evaluated angiotensin II (Ang II)-induced dysfunction in human umbilical vein endothelial cells (HUVECs), and the effects of atorvastatin (Ator) on induced HUVECs in vitro. The cytotoxicity of Ang II and Ator was determined by the MTT assay. A series of cellular responses were screened, including oxidative stress, cellular apoptosis, inflammatory response, autophagy, expression of endothelial nitric oxide sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Although the primary uses of atorvastatin and other statins are for the treatment of dyslipidemia, the beneficial effects in the cardiovascular system may go beyond the cholesterol鈥恖owering effects to target other cholesterol鈥恑ndependent effects, such as improving endothelial functions and attenuating vascular remodelling [7,20,21]. Atorvastatin has been reported to reverse the dysfunction of human umbilical vein endothelial cells induced by angiotensin II [21]. Interestingly, studies also show that atorvastatin induces endothelial dysfunctions via inhibition of endothelium tube formation and migration [10,22].…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary uses of atorvastatin and other statins are for the treatment of dyslipidemia, the beneficial effects in the cardiovascular system may go beyond the cholesterol鈥恖owering effects to target other cholesterol鈥恑ndependent effects, such as improving endothelial functions and attenuating vascular remodelling [7,20,21]. Atorvastatin has been reported to reverse the dysfunction of human umbilical vein endothelial cells induced by angiotensin II [21]. Interestingly, studies also show that atorvastatin induces endothelial dysfunctions via inhibition of endothelium tube formation and migration [10,22].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 1 渭 mol/L atorvastatin enhanced VEGF and IL8 promoter activities but decreased their production by human microvascular endothelial cells in hypoxia [31]. Furthermore, Dang and coworkers showed that 10 渭 mol/L atorvastatin did not affect tube formation by HUVEC in an overnight stimulation [32]. Atorvastatin also decreased endothelial senescence and dysfunction induced by angiotensin II [32].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Dang and coworkers showed that 10 渭 mol/L atorvastatin did not affect tube formation by HUVEC in an overnight stimulation [32]. Atorvastatin also decreased endothelial senescence and dysfunction induced by angiotensin II [32]. On the other hand, atorvastatin administered orally inhibited inflammatory angiogenesis and production of VEGF in sponge transplants in mice [33].…”
Section: Discussionmentioning
confidence: 99%
“…Ang II induces cardiomyocyte hypertrophy, heart damage, and fibrosis [73]. Dang et al鈥檚 [74] data suggest that Ang II also causes oxidative stress, inflammation, and mitochondrial damage, which leads to apoptosis and endothelial senescence. The binding of Ang II to the AT1 receptor can cause apoptosis of cardiomyocytes, resulting in a series of complex reaction processes such as decreased Bcl-2/Bax and caspase-3 activation [75].…”
Section: Ventricular Remodeling and Mir-30 Familymentioning
confidence: 99%